Changeability of Manufacturing Automation Systems using an Orchestration Engine for Programmable Logic Controllers. Issue 3 (2015) - Bührer, Ulrich T.; Legat, Christoph; Vogel-Heuser, Birgit
Abstract: To allow companies of the manufacturing domain to satisfy customer demands and withstand increasing global competition, production automation processes have to become more efficient, stable and flexible. For this purpose, aspects of changeability and adaptiveness of automation systems have to be considered. Within this paper, a concept for an Orchestration Engine is proposed, which aims at providing the required degrees of flexibility within the field level control software. This Orchestration Engine is able to flexibly adapt its behavior during operation and is also able to adapt to physical changes of the production environment. For the implementation of this approach, existing concepts and technologies of model-driven engineering are utilized as a starting point for system modelling and automatic code generation, which is realized by model to text transformations. In order to allow application of the proposed concept to existing PLCs, requirements of the predominant IEC 61131-3 standard, such as cyclic execution, are taken into account.